Mercury speciation and subcellular distribution in experimentally dosed and wild birds. (18th August 2017) - Perkins, Marie; Barst, Benjamin D.; Hadrava, Justine; Basu, Niladri
Abstract: Many bird species are exposed to methylmercury (MeHg) at levels shown to cause sublethal effects. Although MeHg sensitivity and assimilation can vary among species and developmental stages, the underlying reasons (such as MeHg toxicokinetics) are poorly understood. We investigated Hg distribution at the tissue and cellular levels in birds by examining Hg speciation in blood, brain, and liver and Hg subcellular distribution in liver. We used MeHg egg injection of white leghorn chicken ( Gallus gallus domesticus ), sampled at 3 early developmental stages, and embryonic ring‐billed gulls ( Larus delawarensis ) exposed to maternally deposited MeHg. The percentage of MeHg (relative to total Hg [THg]) in blood, brain, and liver ranged from 94 to 121%, indicating little MeHg demethylation. A liver subcellular partitioning procedure was used to determine how THg was distributed between potentially sensitive and detoxified compartments. The distributions of THg among subcellular fractions were similar among chicken time points, and between embryonic chicken and ring‐billed gulls. A greater proportion of THg was associated with metal‐sensitive fractions than detoxified fractions. Within the sensitive compartment, THg was found predominately in heat‐denatured proteins (∼42–46%), followed by mitochondria (∼15–18%). A low rate of MeHg demethylation and high proportion of THg in metal‐sensitive subcellular fractions further indicates that embryonic and hatchling time points are Hg‐sensitive developmental stages, although further work is needed across a range of additional species and life stages. Environ Toxicol Chem 2017;36:3289–3298. © 2017 SETAC